Effect of Rehabilitation Setting on Dependence Following Stroke: An Analysis of the French Inpatient Database. (January 2014) - Schnitzler, Alexis; Woimant, France; Nicolau, Javier; Tuppin, Philippe; de Peretti, Christine
Background . In France in 2009, patients admitted to Multidisciplinary Inpatient Rehabilitation for stroke were sent to a neurological rehabilitation center (NRC) or a general or geriatric rehabilitation (GRC) service. Objective . To describe the functional outcome of stroke patients admitted for rehabilitation in France in 2009, both globally and as a function of the rehabilitation setting (GRC or NRC). Methods . Data from the French Hospital Discharge Diagnosis databases for 2009 were included. Two logistic regression models were used to analyze factors related to improvement in dependence score and discharge home. Odds ratios (ORs) were also calculated. Results . Among the 83 505 survivors of acute stroke in 2009, 28 201 were admitted for rehabilitation (33.8%). Of these, 19 553 went to GRC (69%) and 8648 to NRC (31%). On average, patients admitted to GRC were older (78.6 years vs 66.4 years), P < .001). At the start of rehabilitation, 50% of NRC patients and 56% of GRC patients were heavily dependent, but level of dependence was similar within each age-group. Rehabilitation in NRC lead to a greater probability of functional improvement (OR = 1.75, P < .001) and home discharge (OR = 1.61, P < .001) after adjustment for gender, age, Charlson's comorbidity index, initial level of dependence, type of stroke, and total length of stay. Conclusion . This study confirms, on a national level, the functional benefit of specialized rehabilitation in NRC. These results should be useful in the improvement of care pathways, organization of rehabilitation, and discharge planning.